Making the Move or Keeping the Connection? Engineering Women as Managers - an Australian Study - Marinelli, Melissa (2011)
This paper describes the initial stages of current research exploring the advancement of women engineers to managers and leaders in technical organizations in Australia. The aim of the research is to provide an understanding of women engineers' transition to manager and leader from the perspective of those that have lived through this experience. In doing so, it extends existing research on women in non-traditional work, management and leadership and engineering practice. The voice provided by the study broadens and enhances the view of management and leadership in engineering. By focusing on successful transitions, the research findings can inform policy and practice to retain and advance women in engineering - a profession in which women are overwhelmingly underrepresented. The study uses a qualitative research design guided by phenomenological and feminist perspectives. In depth semi-structured interviews have been used to capture the experiences of women working in non-traditional, male dominated workplaces. This paper presents preliminary analysis of an initial set of eight interviews and focuses specifically on the transition to manager. It explores emerging themes relating to the participant's newfound roles as managers - Technical Competence, Retaining the Technical Link and Me as Manager. These themes highlight aspects of the participants' experience of becoming a manager. They also reveal how management is conceptualised in engineering, specifically by women engineers who have advanced to senior positions in the engineering profession, and begin to inform a broader and more inclusive view of management in the engineering profession.